PENGARUH MODEL TPS TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATERI REDOKS - Zakia, Zakia; Masriani, Masriani; Enawaty, Eny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe purposes of this study were to determine differences of activities and learning outcomes between students were taught using Think Pair Share (TPS) Cooperative learning model and conventional method and effect of applying Think Pair Sharecooperative learning model toward learning outcomeson redox materials at X Grade of IPA SMAN 1 Sungai Raya. Quasi-experimental with nonequivalent control group design was used as research method. The samples were students X IPA 4 as control class and X IPA 2 as experimental class that were determined with random sampling technique. Activities and outcomes learning were analyzed using U-Mann Whitney. The result of data analysis showed that differences activities and learning outcomes beetwen students were taught using cooperatif learning model Think Pair Share type and conventional method. Think Pair Share cooperative learning model give effect with value of 33,89 % on increasing students learning outcomes.  Keyword: Think Pair Share, activities, learning outcomes, redox